Association between Body Mass Index and Hamstring Flexibility among Indian Doctors - Harpreet S Gulati; Ambica Wadhwa; Kamaljeet Kaur; Jasveen Kaur; Mamta Sharma (Journal of Medical Academics)
Introduction: Clinicians in the current scenario are persistently exposed to a heavy workload and an enormous degree of stress, which can hamper the musculoskeletal component of the body significantly. The health of doctors is a critical component in the goal of creating a disease-free society since they form a resolute pillar of the healthcare sector. Aim of the study: The objective was to determine the effect of body mass index on hamstring flexibility in clinicians. This will establish a relationship between obesity and body stretchability. Materials and methods: The study was conducted in outpatient department (OPD) clinics of various departments at Punjab Institute of Medical Sciences, Jalandhar, and OPDs of NIMS Hospital, Jaipur, over a period of 2 years from July 2019 to June 2021. BMI was calculated as the ratio of weight (kg) to the square of height (m). Hamstring flexibility was checked by obtaining the sit-and-reach test score using a sit-and-reach test box. Results: Body flexibility reduced significantly with advancing age and increasing body mass index (BMI). Above-average back and hamstring flexibility was seen in only 8.5% of the doctors, while 12% of the clinicians demonstrated poor flexibility range. Conclusion: The present study yields a significant association in terms of linear correlation between hamstring flexibility and obesity among clinicians. The professionals can take note of this information and use it as caution to protect their own health.